2D velocity trajectories of Hα spicules - Khutsishvili, E.; Kvernadze, T.; Kulijanishvili, V.; Ograpishvili, N.; Korol, A.; Khutsishvili, D. (Известия Крымской астрофизической обсерватории, 2011)
Hα and D3 spicule spectrograms for 3.800–9.300 km heights in the solar chromosphere were obtained using the 53-cm large non-eclipsing coronagraph of the Abastumani Astrophysical Observatory during 1982. Spectrograms in Hα line were obtained in the second series of the spectrograph, where the reversed dispersion is equal to 0.96 Å/mm, while spectrograms in D3 line were obtained in the third series of the spectrograph, where the reversed dispersion equals 0.58 Å/mm. For Hα spicules we obtained 250 series of spectrograms during 44 min each consisting of 8 different chromospheric heights starting from 3800 km up to 8700 km reaching about 2000 spectrograms altogether. Similarly, for D3 spicules we obtained 100 series of spectrograms during 30 min each consisting of 8 different chromospheric heights starting from 4400 km up to 9300 km reaching about 800 spectrograms altogether. On the basis of these spectrograms radial and tangential velocities were measured for a dozen of selected clearly identified spicules. It could be clearly stated that: i) a spicule motion in 2D velocity space generates a trajectory cloud which is prolonged in the tangential velocity direction with a ratio of axes equal to 2.7; ii) the spatial motion of spicules seems to be rather chaotic than oscillating.